PENGARUH AUDIT MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PADA PT.POS INDONESIA (PERSERO) KANTOR CABANG UTAMA BANDUNG - Fitrilia Diah Ayu Erlina; Widwi Handari Adji (LPSDI Bina Patria, 2023)
The purpose of this study was to determine the extent of the influence of human resource management audits on employee performance at PT Pos Indonesia (Persero) at the Bandung Head Office. The method used by researchers is quantitative, where the data collection method is to distribute questionnaires through Google Form to 55 employees who are respondents, the data obtained is then analyzed with the SPSS V.25 program. The results of this study indicate that